Emerging Themes in Information Systems and Organization Studies - Carugati, Andrea; Rossignoli, Cecilia; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2011)
This book consists of an anthology of writings. The aim is to honour Marco to celebrate the 35th year of his academic career . The book consists of a collection of selected opinions in the field of IS. Some themes are: IT and Information Systems organizational impacts, Systems development, Business process management, Business organization, e-government, social impact of IT.
Keywords: Economics; Information systems; Information Systems; Business planning; Management information systems; Economics/Management Science; Business Information Systems; Management of Computing and Information Systems; Information Systems Applications (incl.Internet).; Organization/Planning.